MANIPULATIVE BEHAVIOR IN THE PROFESSIONAL ACTIVITIES OF OFFICE STAFF - Ivan Romanovych Krupnyk; Natalya Viktorivna Tkalenko (Insight: the psychological dimensions of society, 2019)
Purposes. Coverage of manipulative behavior in the professional activities of office workers working in the “man-man”. It is also important to study this phenomenon in dynamics, so the survey involved respondents of different ages.Methods. General theoretical: analysis, synthesis of the provisions contained in the psychological literature on the psychology of manipulation, comparison, generalization, interpretation and systematization of theoretical and empirical research; Empirical: methodology “Study of Machiavellian personality” (adaptation. Symbolic), to identify the level of propensity of the individual to manipulative behavior. The goal of the method: identifying makovelski attitudes and beliefs of the subjects. Methods of mathematical statistics, in particular the Fisher angular transformation criterion, were also used.Results and conclusions. The analysis revealed that the percentages of the survey results in the two samples differ significantly. In particular, a high level of manifestation of manipulative behavior in a sample of subjects aged 20–25 years was not revealed. In addition, the average level with a tendency to high in this age group also occupies a smaller proportion. The personality begins to learn to interact, to communicate in a new social role and in a new activity – labor. The young specialist observes, adapts, adapts to the new environment more than influences him. But, in the sample of the studied 26–44 years – a high level was found in twenty percent. Thus, manipulation as a type of behavior prevails in the sample of respondents aged 26–44 years. This suggests that older specialists are convinced that when communicating with other people they can and should be manipulated, they have the skills and specific skills to manipulate. The results of the study showed that adult respondents are more prone to manipulative behavior. This is due to the fact that an adult has an impressive Arsenal of manipulative techniques, it is understood where and how they can be used, have the skills and specific skills to manipulate. The differences in the use of manipulations between respondents of different age groups, allow us to trace the dynamics of the formation of interpersonal relationships in teams.